Experimental study of needle–tissue interaction forces: Effect of needle geometries, insertion methods and tissue characteristics - Jiang, Shan; Li, Pan; Yu, Yan; Liu, Jun; Yang, Zhiyong (Journal of biomechanics, 2014)
A thorough understanding of needle–tissue interaction mechanics is necessary to optimize needle design, achieve robotically needle steering, and establish surgical simulation system. It is obvious that the interaction is influenced by numerous variable parameters, which are divided into three categories: needle geometries, insertion methods, and tissue characteristics. A series of experiments are performed to explore the effect of influence factors (material samples n=5 for each factor) on the insertion force. Data were collected from different biological tissues and a special tissue-equivalent phantom with similar mechanical properties, using a 1-DOF mechanical testing system instrumented with a 6-DOF force/torque (F/T) sensor. The experimental results indicate that three basic phases (deformation, insertion, and extraction phase) are existent during needle penetration. Needle diameter (0.7–3.2mm), needle tip (blunt, diamond, conical, and beveled) and bevel angle (10–85°) are turned out to have a great influence on insertion force, so do the insertion velocity (0.5–10mm/s), drive mode (robot-assisted and hand-held), and the insertion process (interrupted and continuous). Different tissues such as skin, muscle, fat, liver capsule and vessel are proved to generate various force cures, which can contribute to the judgement of the needle position and provide efficient insertion strategy.